Epidemiology and healthcare access in Brazilian multiple sclerosis patients: insights from the BRANDO database - Damasceno, Alfredo; Ramari, Cintia; Tauil, Carlos; Sato, Henry Koiti; Callegaro, Dagoberto; Mendes, Maria Fernanda; D'Almeida, José Artur Costa; Diniz, Denise Sisterolli; Nascimento, Osvaldo J. M.; Parolin, Laura; Fukuda, Thiago; Gama, Paulo; Neto, Herval Soares; Lana-Peixoto, Marco; Passos, Giordani Rodrigues dos; Caetano, Rayllene; Santos, Kleber Cavalcante; Disserol, Caio César Diniz; Vieira, Gabriel de Deus; Silva, Guilherme Diogo; Cunha, Eliana; Talim, Natália; Wagner, Mario B.; Pitombeira, Milena Sales; Becker, Jefferson (Arquivos de Neuro-Psiquiatria, 2025)
Multiple sclerosis (MS) is an inflammatory and neurodegenerative disorder whose prevalence varies across Brazil (from 15–27 cases per 100 thousand inhabitants), and the absence of an extensive national study limits the understanding of MS epidemiology in a nation as diverse as Brazil.To compare epidemiological data, including healthcare access, among people with MS across four Brazilian regions.Data from 2,974 Brazilian MS patients in the Collaborative Latin American Database for Multiple Sclerosis (BRANDO) were analyzed. We assessed demographic and clinical outcomes, as well as healthcare access, to elucidate regional differences.The cohort was predominantly composed of female patients (72.5%) with MS onset at a mean age of 30.6 years. Regarding the regional differences, there was a lower predominance of female patients (68.7%; p = 0.003) in the Southeast, a higher rate of subjects of mixed ethnicity (p < 0.001) in the Midwest (40.3%) and Northeast (63.7%), higher scores on the Expanded Disability Status Scale (EDSS) in the Northeast (4.0; p < 0.001), a higher prevalence of relapsing-remitting MS (RRMS) in the Southeast and Midwest (87%; p < 0.001), while the Northeast presented (p < 0.001) the highest rates of primary progressive MS (PPMS) and secondary progressive MS (SPMS) (PPMS = 15.8%; SPMS = 18%). The Northeast presented the longest time (5.9 years; p < 0.01) from disease onset until MS diagnosis (range for the other regions = 1.9–3.7 years). And the Midwest showed the shortest time (2.1 years; p < 0.01) from disease onset until first access to disease-modifying therapies (DMTs; range for the other regions = 3.5–5.1 years).The present is the first nationwide epidemiological study on people with MS in Brazil. It underscores regional epidemiological variations and differences in healthcare access, advocating for tailored approaches in MS management and research.
Keywords: Multiple Sclerosis; Latin America; Epidemiology; Health Inequities; Nervous System Diseases; Demography